Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Dengan Motivasi Kerja Sebagai Variabel Intervening: Pada Pegawai Kantor Kesyahbandaran Dan Otoritas Pelabuhan Kelas II Jayapura - Rambet, John Ryan Ardiles; Syauta, Jack H.; Ratang, Westim (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2024)
This study aims to analyze the influence of work discipline and work environment on employee performance, with work motivation as an intervening variable, at the Harbormaster’s Office and Class II Port Authority in Jayapura. A quantitative research approach was employed, utilizing Structural Equation Modeling-Partial Least Square (SEM-PLS) to examine the relationships between variables. Data were collected through questionnaires distributed to employees as research respondents. The findings indicate that both work discipline and work environment have a positive and significant effect on work motivation. Furthermore, work motivation has a positive and significant impact on employee performance. Work discipline also directly influences performance, while the work environment affects performance indirectly through work motivation. These results highlight the role of work motivation as an intervening variable that strengthens the relationship between work discipline and work environment with employee performance. Thus, enhancing work discipline and fostering a supportive work environment can serve as effective strategies to improve employee performance.